The Bible in Greek translation, transmission, and theology of the Septuagint - Kreuzer, Siegfried 1949- (SBL Press, 2015)
"This volume presents English and German papers that give an overview on important stages, developments, and problems of the Septuagint and the research related to it. Four sections deal with the cultural and theological background and beginnings of the Septuagint, the Old Greek and recensions of the text, the Septuagint and New Testament quotations, and a discussion of Papyrus 967 and Codex Vaticanus"...
Includes bibliographical references and index
Keywords: Bible -- Old Testament -- Greek -- Versions -- Septuagint; Bibel -- Altes Testament -- Septuaginta; Bibel; Aufsatzsammlung